Association between perceived stress, emotional eating, and adherence to healthy eating patterns among Saudi college students: a cross-sectional study - Israa M Shatwan; Manar A. Alzharani (Journal of Health, Population and Nutrition, 2024)
Abstract Background College students are vulnerable to high perceived stress (PS) and emotional eating (EE) levels, which are associated with their food consumption. In this study, we aimed to examine the links between perceived stress, emotional eating, and adherence to a healthy eating index. Furthermore, we aimed to test whether sociodemographic data and health measures, including body mass index and physical activity, are associated with perceived stress, emotional eating, or healthy eating index. Methods This study included students from King Abdulaziz University. The participants completed validated perceived stress, emotional eating, and short healthy eating index surveys via an online questionnaire from September to December 2022. Univariate linear regression analysis was performed to examine the association between perceived stress, emotional eating, and adherence to healthy eating index using the short healthy eating index. Results Of 434 students (49.8% male, mean age 21.7 ± 3.0 years), 11.3% had low, 72.0% moderate, and 16.7% high perceived stress. Students with moderate perceived stress had the highest short healthy eating index score (P = 0.001), outperforming those with low and high perceived stress for fruit juice (P = 0.002), fruits (P $$\:<$$ 0.001), vegetables (P=0.03), greens and beans (P<0.001), whole grains (P=0.009), and seafood/plant proteins (P = 0.001) consumption. Also, emotional eating was significantly associated with short healthy eating index score (P = 0.04), fruit juice (P = 0.01) fruit consumption (P<0.001), added sugar (P=0.02) and saturated fatty acids (P = 0.03). Academic major was associated with perceived stress (P = 0.006) and emotional eating (p=0.04). Higher physical activity levels were associated with low perceived stress levels (P<0.001) and high short healthy eating index score (P=0.001), while high body mass index was associated with high emotional eating score (P<0.001). Conclusions The findings confirmed that students are highly vulnerable to moderate and high perceived stress levels. Furthermore, high perceived stress is inversely associated with adherence to a healthy eating index, especially for fruits, vegetables, greens and beans, whole grains, and seafood and plant proteins consumption. Emotional eating, also, associated with students dietary pattern. Physical activity will be beneficial for reducing the level of perceived stress and improving overall dietary patterns.